High risk behaviors and sexually transmitted infections among men in Tanzania. - Ghebremichael, Musie; Paintsil, Elijah (AIDS and behavior, 2011)
We assessed the association between risk behaviors and sexually transmitted infections (STIs) among men. We interviewed 794 men randomly selected from Moshi district of Tanzania. Blood and urine samples were tested for STIs. About 46% of the men tested positive for at least one STI including human immunodeficiency virus (HIV-1), herpes simplex virus (HSV-2), syphilis, chlamydia, trichomonas, and mycoplasma infection. Multiple sexual partners, casual sex, alcohol abuse, and older age were associated with higher odds of having an STI. Effective STI prevention programs in sub-Saharan Africa should have components aimed at addressing modifiable risk behaviors in men.
Keywords: Adult; Alcoholism; Cross-Sectional Studies; Herpes Genitalis; Herpesvirus 2, Human; HIV Infections; HIV-1; Humans; Male; Middle Aged; Population Surveillance; Prevalence; Risk Factors; Risk-Taking; Sexual Behavior; Sexual Partners; Sexually Transmitted Diseases; Socioeconomic Factors; Tanzania; Young Adult